Association Among Obesity, Metabolic Health, and the Risk for Colorectal Cancer in the General Population in Korea Using the National Health Insurance Service–National Sample Cohort. Issue 11 (November 2017) - Shin, Cheol Min; Han, Kyungdo; Lee, Dong Ho; Choi, Yoon Jin; Kim, Nayoung; Park, Young Soo; Yoon, Hyuk
Abstract : BACKGROUND: In Korea, the incidence of colorectal cancer has increased and obesity is on a rising trend because of a Westernized lifestyle in men. OBJECTIVE: The purpose of this study was to evaluate the relationship between metabolic health status, as well as BMI, and the incidence of colorectal cancer. DESIGN: This was a prospective cohort study. SETTINGS: The study was conducted with the National Health Insurance Service–National Sample Cohort. PATIENTS: A total of 408, 931 Korean adults without cancer at baseline were followed up until 2013 (mean follow-up, 9 y). MAIN OUTCOME MEASURES: Demographic, anthropometric, and laboratory data at baseline were collected and categorized. The presence of diabetes mellitus, hypertension, and dyslipidemia was defined using the criteria of previous studies. The incidence of colorectal cancer was also defined according to the International Classification of Disease, 10 th Revision, codes and the claim data on endoscopy with biopsy. RESULTS: During the follow-up, 5108 new cases of colorectal cancer occurred. Being underweight (<18.5 kg/m 2 ) reduced the risk for colorectal cancer among women (adjusted HR = 0.646 (95% CI, 0.484–0.863)), whereas high BMI significantly increased the risk in men and in the elderly. Obesity (≥25 kg/m 2 ), diabetes mellitus, and hypertension were identified as risk factors for colorectal cancer in men but not for women. Although metabolically unhealthy nonobese men had a higher risk for colorectal cancer than metabolically healthy nonobese men (adjusted HR = 1.114 (95% CI, 1.004–1.236)), the risk was lower than that in the obese men. LIMITATIONS: The study population consisted of people who underwent health examinations, thus there could be selection bias. CONCLUSIONS: In Korean adults, obesity contributes to the incidence of colorectal cancer with a sex difference. Nonobese but metabolically unhealthy men are considered to be a high-risk group for colorectal cancer, but obesity itself is more important in colorectal carcinogenesis. SeeVideo Abstract athttp://links.lww.com/DCR/A475 . Abstract : Supplemental Digital Content is available in the text.